Scooby-Doo!. Wrestlemania mystery [videorecording (DVD)] - Vietti, Brandon, 1974-; Welker, Frank; Cohn, Mindy, 1966-; DeLisle, Grey; Lillard, Matthew, 1970- ([publisher not identified], 2014)
When Shaggy and Scooby win tickets to WrestleMania, the entire gang travels in the Mystery Machine to WWE City to attend the epic event. However, when a mysterious ghostly bear appears and threatens to ruin the show, Scooby, Shaggy, Velma, Daphne and Fred work with WWE Superstars to solve the case.